An Electromagnetic Fiber Acoustic Transducer with Dual Modes of Loudspeaker and Microphone. Issue 45 (4th October 2021) - Zou, Junyi; Ling, Feiyao; Shi, Xiang; Xu, Kailiang; Wu, Huiyang; Chen, Peining; Zhang, Bo; Ta, Dean; Peng, Huisheng
Abstract: A flexible fiber acoustic transducer is created by designing a parallel configuration of a Rubidium iron boron (NdFeB) magnet fiber and an aluminum fiber. The former provides a stable magnet field, while the latter vibrates to phonate upon applying alternating current or generates alternating voltage in the sound field. This single device exhibits dual functions as a loudspeaker or a microphone. As a fiber loudspeaker, it can generate 40–60 dB of audible (20 Hz−20 kHz) and directional sounds which can be used for blind navigation and controllable sound field distribution. The fiber acoustic transducer functions as a microphone when external sound waves force the aluminum fiber to vibrate. After the fiber microphones are woven into several different positions of a piece of clothing, the sound source can be accurately located based on the time differences reaching different microphones. This wearable fiber acoustic transducer is promising to be used to quickly search people in trouble during emergency rescue activities such as earthquakes or fires. Abstract : A fiber acoustic transducer is created by designing aluminum fiber on NdFeB magnet. The unique flexible fiber configuration allows for the directional sounds for blind navigation and a controllable sound field distribution, while the position of sound source can be located after woven into clothes at different positions.